Contribution of Quality Assurance and Standards Officers’ in Enhancing Kenya Certificate of Secondary Education Performance in Kwanza SubCounty - Sululu, Peter; Ochieng, Pamela; Kirwok , Emily (African Journal of Education,Science and Technology (AJEST), 2022)
The purpose of this study was to determine the contribution of Quality Assurance and Standards Officers‟ (QASOs) in Enhancing Kenya Certificate of Secondary Education performance in Kwanza Sub-County. The study was founded on Role theory developed by Mullin (2004). The study utilized a descriptive survey research design. The target population comprised of 319 teachers, 35 principals and 2 QASOs. Simple random sampling technique was used to sample 95 teachers, 11 principals and purposive sampling technique was used to select 2 QASOs. Iinterview schedules were used to collect data from QASOs. Questionnaires were used to collect data. Data collected was analyzed using both inferential and descriptive statistics. Results indicated that QASOs typically enhance staff growth and development, educational and learning materials. QASOs also play an important role in the development of educational programs in the Kwanza Sub- County. Further, they provide advice and feedback on how to run the curriculum, and indicating that the curriculum has been implemented. It was determined that QASOs play a significant role in ensuring proper curriculum implementation in schools. The report suggests that QASOs should be bolstered by providing them with more resources. QASOs should monitor schools more frequently and develop a follow-up system to guarantee that their suggestions, among other recommendations are executed.